Effect of Night-Time Noise Control Combined with Detailed Nursing on Negative Emotions and Sleep Quality in Patients with Upper Gastrointestinal Bleeding - Jing Yu; Dongyan Xu; Lihui Zhou (Noise and Health)
Objective: The aim of the study was to investigate the effect of nighttime noise control, combined with detailed nursing, on negative emotions and sleep quality in patients suffering from upper gastrointestinal bleeding. Methods: This retrospective analysis was conducted on 100 patients with upper gastrointestinal bleeding who were admitted to the Fifth People’s Hospital of Wuxi from January 2021 to January 2024. Patients were divided into the noise control group and the detailed nursing group based on different nursing care methods, with each group containing 50 cases. The detailed nursing group received detailed nursing, whereas the noise control group received nighttime noise control combined with detailed nursing. The results of the Fear Visual Analog Scale (FVAS), Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety Rating Scale (HAMA), Hamilton Depression Rating Scale (HAMD), and subjective assessment of noise of the two groups were compared. Results: After management, the HAMA, HAMD, FVAS, and PSQI scores of both groups showed a significant decrease compared to baseline (P < 0.05). Additionally, the HAMA, HAMD, FVAS, and PSQI scores of the noise control group were significantly lower than those of the detailed nursing group (P < 0.05).The subjective assessment of noise in both groups was significantly higher after management than before management, with the noise control group reporting a significantly higher subjective noise assessment than the detailed nursing group (P < 0.05). Conclusion: Nighttime noise control combined with detailed nursing is effective in patients with upper gastrointestinal bleeding. This approach helps reduce negative emotions such as anxiety, depression, and fear; lowers the subjective assessment of noise; and improves sleep quality.